Psychometric properties of the Social and Emotional Learning Scale: Social Skills Improvement System (SSIS SEL) - Alquwaie, Norah Abdulaziz; Alwatban, Mohammad Sulaiman (Journal of Educational and Psychological Sciences, 2025)
This study aimed to validate the Social and Emotional Learning Scale: Social Skills Development System, an instrument designed to measure social and emotional learning (SEL) in educational settings (Gresham & Elliott, 2008). (677) secondary school students in Hail completed (SSIS SEL). The study approach is the descriptive. The methodology comprised two primary analytical procedures: an evaluation of the scale’s internal consistency using Cronbach’s alpha and the Weighted Omega coefficient, and a confirmatory factor analysis to assess the model fit of the scale’s structure. The results revealed that the scale exhibited high internal consistency, with a Cronbach’s alpha coefficient of (0.934) and a Weighted Omega coefficient of (0.933). The confirmatory factor analysis confirmed the five-factor structure of the scale, with each dimension meeting the quality criteria for model fit. In conclusion, this study supports the Social and Emotional Learning Scale: Social Skills Development System as a valid and reliable tool for assessing SEL in educational settings. Future studies are recommended to investigate the scale’s applicability across different cultural contexts and its relationship with other educational outcomes.